To make a long story short: Andrée Levésque - Valobra, Adriana María (2024)
The following is the transcription of an interview to the Canadian feminist historian Andrée Lévesque, made by Argentinian historian Adriana Valobra in 2023, at the Archives Passe-Mémoire in Quebec, founded by Levésque in 2010. Descentrada offers a Spanish translation of the text, following the original version in English.